Divergência interpopulacional e interespecífica e processo seletivo atuante nos genes ortólogos a fruitless e Odysseus em Drosophila mojavensis e D. arizonae - Santos, Wellington dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Despite having been intensively studied, many questions about the process of speciation remain unanswered, especially regarding genetic changes that lead to reproductive isolation. In this study we analyzed two genes candidates for speciation genes, fruitless (fru) and Odysseus (OdsH) in two closely related cactophilic Drosophila species, D. mojavensis and D. arizonae, which diverged from a common ancestor less than 1 million years ago. The fru gene plays a predominant role in the specification of the potential for sexual behavior of Drosophila male, thus influencing the pre-zygotic isolation. OdsH, a gene with a homeodomain that has undergone rapid evolution in the melanogaster subgroup of species, has been associated to hybrid sterility in Drosophila. Sequences of these two genes, known to be variable in Drosophila and other insects, were amplified and sequenced in four strains of D. mojavensis and two of D. arizonae. Analyses of diversity, selection tests and phylogenetic analyses were performed. Both genes show low diversity between the sequences from the two species, which is consistent with the recent divergence between them. The selection tests performed for the sequences showed that the fragments analyzed of both genes are under purifying selection, which is consistent with data in other Drosophila species considering the fru gene, but is different from data for OdsH in species of the subgroup melanogaster, in which is under positive selection. Phylogenetic relationships reconstructed for the sequences of the two genes, as well as networks of haplotypes allowed to make inferences about the evolutionary history of species and populations. Analyzes of Neighbor Joining and Maximum Likelihood clustered all the sequences of D. mojavensis in a monophyletic clade, as well as the sequences of each of its strains, reinforcing the classification of subspecies for the populations from where they were colected. However, the monophyly...

A despeito de ter sido intensivamente estudado, muitas das questões sobre o processo de especiação ainda permanecem sem respostas, principalmente em relação às alterações genéticas que conduzem ao isolamento reprodutivo. Neste trabalho foram analisados dois genes candidatos a genes de especiação, fruitless (fru) e Odysseus (OdsH), em duas espécies cactofílicas estreitamente relacionadas de Drosophila, D. mojavensis e D. arizonae, que divergiram de um ancestral comum a menos que 1 milhão de anos atrás. O gene fru exerce um papel predominante na especificação do potencial para o comportamento sexual de machos de Drosophila, podendo influenciar no isolamento reprodutivo pré-zigótico. O gene OdsH, que contém um homeodomínio que sofreu rápida evolução no subgrupo melanogaster, associa-se a esterilidade híbrida em Drosophila. Foram amplificados e sequenciados fragmentos destes genes em quatro linhagens de D. mojavensis e duas de D. arizonae e realizadas análises de diversidade, testes de seleção e análises filogenéticas. Ambos os genes apresentaram baixa diversidade entre as sequências das duas espécies, o que está de acordo com a divergência recente entre elas. Os testes de seleção realizados para as sequências de ambos os genes revelaram que os fragmentos analisados estão sob seleção purificadora, o que está de acordo com dados em outras espécies de Drosophila considerando o gene fru, mas é diferente do observado no subgrupo melanogaster para o gene OdsH, onde o gene mostra sinal de seleção positiva. As relações filogenéticas reconstruídas para as sequências dos dois genes, bem como redes de haplótipos permitiram fazer inferências sobre a história evolutiva das espécies e suas populações. Análises de Neighbor Joining e de Máxima Verossimilhança agruparam todas a sequências de D. mojavensis em um clado monofilético, como também as sequências de cada uma de suas linhagens corroborando...
Keywords: Genética; Inseto - Filogenia; Drosófila - Genética; Drosófila mojavensis; Drosófila arizonensis